Comparative Analysis of Chloroplast Genomes of Thalassiosira Species - Liu, Kuiyan; Chen, Yang; Cui, Zongmei; Liu, Shuya; Xu, Qing; Chen, Nansheng (Frontiers in Marine Science, 2021)
Thalassiosira is a species-rich genus in Bacillariophyta with important ecological contribution to primary productivity but can also pose negative impact on ecology by developing harmful algal blooms (HABs). However, genomic resources of only a few Thalassiosira species are currently available. Here, we constructed complete chloroplast genomes (cpDNAs) of six Thalassiosira strains (representing six Thalassiosira species T. rotula, T. profunda, T. nordenskioeldii, T. tenera, T. weissflogii, and Thalassiosira sp.), and compared them with published cpDNAs of other diatoms. Comparative analysis revealed that Thalassiosira cpDNAs have generally conventional and conserved quadripartite structure with important exceptions. Gene orders of cpDNAs of Thalassiosira sp. (CNS00561) and T. oceanica were different from that of other Thalassiosira species. Additionally, endosymbiotic gene transfers (EGT) were found to occur in the evolution of Thalassiosira cpDNAs. Furthermore, genomic regions of cpDNAs were found to be highly variable, which could be used to construct molecular markers for distinguishing Thalassiosira species with high resolution and high specificity. This study also demonstrated that Thalassiosira species emerged roughly around 51 MYA and diversified 17–28 MYA. Thalassiosira cpDNAs are not only valuable as super-barcode for phylogenetic analysis, but also important for functional and evolutionary analysis of diatoms.